SEX EDUCATION: EXPOSURE TO CHILDREN THROUGH ISLAMIC APPROACH - Nor Farizah Johari; Nursyahida Zulkifli; Zanirah Mustafa@Busu; Nor Asmira Mat Jusoh (Journal of Islamic, Social, Economics and Development, 2024)
The increasing in birth rate of illegitimate children in Malaysia is getting serious. Statistics showed that from year 2008 till 2010, there were 152, 182 out of wedlock children have been registered under National Registration Department of Malaysia. Out of the numbers, 74, 723 of them are Muslim decedents. In 2007, 2008 and 2009, the number of the illegitimate children born was 16, 100, 16541 and 17, 303 respectively. The latest statistic in 2011 showed that 18, 652 illegitimate children were born. The social problem among Muslim is getting worse despite many programs including sex education has been introduced since primary school. Therefore, the aim of the study is to provide a systematic literature review about the sex education among school children. This paper only provides an overview about the previous studies on sex education and therefore to suggest the future works about the sex education especially in the Muslim countries like Malaysia. From the literature of review, it is found that there is lacking in the studies about the sex education according to the Islamic perspectives. This study can fill the insufficient studies about the sex education and therefore provide an insight for the government especially Ministry of Education to identify the elements that need to be included in drafting sex education policy in Malaysia. The study is hopefully to improvise the existing programs regarding the social problems generally and illegitimate babies born specifically by recommending Islamic approach in solving this adultery problem.